1969
DOI: 10.1139/f69-044
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Temperatures for Great Lakes Rainbow Trout

Abstract: Samples of progeny from wild rainbow trout (Salmo gairdneri) homing to four widely separated Great Lakes watersheds, when incubated and reared under similar conditions and acclimated to 15 C, did not differ in tolerance to upper lethal temperatures. The size of the individual fish under test did not affect the resistance time. The similar response of the four samples to upper lethal temperatures complements the conclusions previously reported from phenotypic observations of wild and cultured trout from the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
2

Year Published

1977
1977
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 2 publications
0
20
2
Order By: Relevance
“…For example, thermal acclimation offsets the effect of acute warming on RMR in 5–7 g Mount Shasta and Eagle Lake O. mykiss (2.3–2.8 mg O 2 kg −0.95 min −1 at 14°C and 2.9–3.1 mg O 2 kg −0.95 min −1 at 25°C; Myrick and Cech, 2000), which would normally double RMR over this temperature range, as observed here. Warm acclimation can also increase upper thermal tolerance limits, as it did for four anadromous Great Lakes populations of juvenile O. mykiss (Bidgood and Berst, 1969). Given that our fish were captured at and, presumably, thermally acclimatized to between 14 and 17°C, it would be of interest to test wild fish with a warmer thermal acclimation history.…”
Section: Discussionmentioning
confidence: 84%
“…For example, thermal acclimation offsets the effect of acute warming on RMR in 5–7 g Mount Shasta and Eagle Lake O. mykiss (2.3–2.8 mg O 2 kg −0.95 min −1 at 14°C and 2.9–3.1 mg O 2 kg −0.95 min −1 at 25°C; Myrick and Cech, 2000), which would normally double RMR over this temperature range, as observed here. Warm acclimation can also increase upper thermal tolerance limits, as it did for four anadromous Great Lakes populations of juvenile O. mykiss (Bidgood and Berst, 1969). Given that our fish were captured at and, presumably, thermally acclimatized to between 14 and 17°C, it would be of interest to test wild fish with a warmer thermal acclimation history.…”
Section: Discussionmentioning
confidence: 84%
“…By comparison, trout of equivalent age fed to satiation over summer (base thermal regime rising from 13°C to 21°C) grew at a rate of approximately 3.0%/d, as did the trout at +2°C in summer (Linton et al 1997). In this summer study, we concluded that the most significant effect of the +2°C warming scenario was the 30% reduction in food intake experienced by the warmed fish in the last 30 d, when water temperatures were approaching their upper lethal maximum (Bidgood and Berst 1969). A significant temperature‐dependent feeding effect was also experienced by the warmed fish of the present study; however, this time their food consumption increased by more than 30%.…”
Section: Discussionmentioning
confidence: 84%
“…The results of the present study clearly demonstrate intraspecific variation in trueM˙O 2max , AAS, FAS, EPOC, O 2crit , ILOS and CT max among three strains of O. mykiss . In contrast, the majority of the previous studies that have independently examined variation in metabolic traits, hypoxia tolerance or upper thermal tolerance among strains of O. mykiss have found little evidence of intraspecific variation (Bidgood & Berst, ; Myrick & Cech, ; Rodnick et al., ; Scott et al., ). For instance, Scott et al .…”
Section: Discussionmentioning
confidence: 93%
“…Intraspecific differences in metabolic rate, aerobic scope, critical oxygen level, hypoxia tolerance and upper thermal tolerance are not novel observations in fish generally and several previous studies have assessed at least one of these traits in domestic or wild strains of O. mykiss from the U.S.A., Canada, Austria, Italy, Australia and Japan (Fry, ; Bidgood & Berst, ; Klar et al., ; Lee & Rinne, ; Wieser et al., ; Scarabello et al., ; Strange et al., ; Alsop & Wood, ; Currie et al., ; McGeer et al., ; Myrick & Cech, , ; Carline & Machung, ; Faust et al., ; Molony et al., ; Rodnick et al., ; Ineno et al., ; Galbreath et al., ; LeBlanc et al., ; Recsetar et al., ; Chen et al., ; Scott et al., ; Verhille et al., ). In particular, these studies have demonstrated substantial variation in upper thermal tolerance, hypoxia tolerance, routine trueM˙O 2 and trueM˙O 2max in O. mykiss , which could be indicative of a large amount of intraspecific variation in this species.…”
Section: Discussionmentioning
confidence: 99%